Morfologia testicular e reserva espermática na codorna japonesa (Coturnix coturnix japonica) - Leonardo Lara e Lanna (2012)
Despite the genetic improvement and growth potential of quail breeding, selection for reproductive traits receives low priority and no reliable parameter is used as a predictor of fertility in quail. The intra-abdominal location of the testes is the main obstacle to the creation of such a parameter. Testicular morphology and sperm reserve in Japanese quail (Coturnix coturnix japonica) were characterized in the present study. Testicular biometry and histomorphometry were determined in birds at 15, 30, 45, and 60 days of age. Gonadal and extragonadal sperm reserve was estimated in sexually rested males and in males submitted toconsecutive matings. Testicular measures and weight were correlated and the viability of testicular ultrasonography was evaluated in birds at 60 days old. Significant difference was found for every parameter evaluated between birds at 15, 30, 45, and 60 days of age. Spermatozoa in the seminiferous tubules lumen were first observed at 30 days old. Thetesticular development stabilized at 45 days, evidenced by the lack of statistical difference in biometric and histomorphometric parameters, compared to males at 60 days of age. The high seminiferous tubules proportion, 91.2% + 4.9 at 60 days old, reinforces the theory that theJapanese quail is adapted to high daily frequency of copulations. The total and daily sperm production per gram of testis was estimated in 537 + 75.6 e 107 + 22.7 x 106, respectively. The gonads were responsible for 68% of the total sperm reserve. There was no reduction of the gonadal and total sperm reserve after consecutive matings. Nevertheless, the extragonadal sperm reserve was lower for males that copulate for five consecutive days. The gonadosomatic index was 3.68% at 60 days of age, superior to that described in the literature. The measures thatbest correlated with testicular weight were the width and thickness of the testes, whereas the thickness of the left testis showed linear correlation coefficient of 0.89 with the total testicular mass. On ultrasonography, the testes were identified as hypoechoic oval structures, surrounded by a thin hyperechoic layer. Testicular length and volume were significantly lower at ultrasound examination when compared to direct measurement with caliper. On the other hand, the thickness was similar among techniques, which indicates that it can be used in the comparison of the reproductive potential between Japanese quail males, since the thickness is highlycorrelated with the testicular weight. The best sonographic approach was by the flank, and with 10MHz linear transducer, which, although presents limitations, can contribute to evaluation and selection of breeders.